Kadar Hambat Ekstrak Daun Salam (Eugenia polyantha Wight) dan Identifikasi Koloni Bakteri Kontaminan pada Sikat Gigi - Megananda Hiranya Putri; Neneng Nurjanah; Eliza Herijulianti; Ulfah Utami (Poltekkes Kemenkes Bandung, 2022)
Toothbrush contamination occurs immediately after use and increases when use is repeated. After the toothbrush is used, it should be washed and disinfected. Bay leaf (Eugenia polyantha Wight) can be an alternative herbal disinfectant because it contains tannin, flavonoids and essential oils that are antiseptic and antimicrobial. This study was an experimental laboratory to see the inhibitory content of bay leaf extract concentration of 20%, 30%, 40%, 50% and 60% on the growth of toothbrush bacteria colonies. Samples are bacterial colonies originating from 8 toothbrushes that have been used by 8 students in the mass toothbrush activity in SDN Harapan in the City of Bandung, with inclusion criteria aged 9-12 years and having a DMF-T index> 3. Repeat treatment for each concentration was 4 times. The results showed that bay leaf extract at concentrations of 20%, 30%, 40%, 50% and 60% could inhibit the growth of bacterial colonies, but when compared with the antibacterial effects produced by antibiotics Ciprofloxacin (5 µg), inhibitory content of bay leaf extract the five concentrations are relatively smaller. Colonies of contaminant bacteria that often appear on toothbrushes are Neisseria sp and Streptococcus sp, Klebsiella sp, Enterobacteriaceae sp (Coliform), and Staphylococcus aureus. Further research can be developed to find out other herbal ingredients that can be combined to increase disinfection, good dosage forms and the right contact time between disinfectant and toothbrushes.